1992
DOI: 10.1177/40.8.1352315
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative image cytometry of hepatocytes expressing gamma-glutamyl transpeptidase and glutathione S-transferase in diethylnitrosamine-initiated rats treated with phenobarbital and/or phthalate esters.

Abstract: Image cytometry was used to quantify the volume of liver expressing two histochemical markers associated with neoplasia, gamma-glutamyl transpeptidase (GGT) and the placental isozyme of glutathione S-transferase (GST-P). Rats were treated with diethylnitrosamine (DENA) followed by phenobarbital (PB), di(2-ethylhexy1)phthate (DEHP), or di-n-octylphthalate (DOP) for 26 weeks. In one series, PBtreated rats were given 2.0%, 0.5%, or 0.1% DEHP in the feed. GGT expression was detected diffusely throughout the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…These findings on hepatocellular carcinomas indicate that some of the carcinomas were negative for GGT. As described above, the result of our study also confirmed the disadvantage pointed out by the previous workers that hepatocellular proliferative lesions observed in HEstained sections could not be always detected in GGT histochemistry [6,7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings on hepatocellular carcinomas indicate that some of the carcinomas were negative for GGT. As described above, the result of our study also confirmed the disadvantage pointed out by the previous workers that hepatocellular proliferative lesions observed in HEstained sections could not be always detected in GGT histochemistry [6,7].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, GGT-negative adenomas were noted in 5 of 6 mice (83%). These findings indicate that hepatocellular adenomas observed in HEstained sections could not be always detected in GGT histochemistry, as demonstrated by the previous histochemical study in rats [6]. Regarding hepatocellular carcinomas stained with HE, 3 of 6 mice (50%) had hepatocellular carcinomas, while 1 of 6 mice (17%) and 3 of 6 mice (50%) had GGT-positive carcinomas and GGT-negative carcinomas, respectively.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Automating the quantitation of BrdU-or TUNEL-labeled cells in normal hepatocytes from rat and mouse liver is described, as well as image analysis of hepatocytes expressing GSTP (Carter et al 1992;Soames et al 1994;Ringer 1995,1996), but automated quantitation of these phenomena within rat hepatic foci has not. Use of automated double labeling techniques described here will permit rapid and accurate assessments of proliferation and apoptosis and may aid efforts aimed at automating the quantitation of the net growth potential of preneoplastic and neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed on sections by the peroxidaseantiperoxidase method, using the antibody against the rGST P. Sections were counterstained with haematoxylin. The number of rGST P-positive foci (consisting of single to several GST P positive cells, indicating preneoplastic lesions) was expressed as per cm 2 of liver sections [16] .…”
Section: Chemicals and Animalsmentioning
confidence: 99%